2013
DOI: 10.1093/hmg/ddt448
|View full text |Cite
|
Sign up to set email alerts
|

Differential, dominant activation and inhibition of Notch signalling and APP cleavage by truncations of PSEN1 in human disease

Abstract: PRESENILIN1 (PSEN1) is the major locus for mutations causing familial Alzheimer's disease (FAD) and is also mutated in Pick disease of brain, familial acne inversa and dilated cardiomyopathy. It is a critical facilitator of Notch signalling and many other signalling pathways and protein cleavage events including production of the Amyloidβ (Aβ) peptide from the AMYLOID BETA A4 PRECURSOR PROTEIN (APP). We previously reported that interference with splicing of transcripts of the zebrafish orthologue of PSEN1 crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 78 publications
(108 reference statements)
6
52
0
Order By: Relevance
“…Consistent with the data of others (Das et al , 2016), FL‐APP and BACE1 co‐migrated partially with a marker for endosomes (Rab7), but not with lysosomal, ER‐intermediate, or MAM markers (Fig 2C). Similarly, the APP‐CTFs C83 and C99 co‐migrated with endosomal and lysosomal markers (Rab5, Rab7, and LAMP‐2) (Haass et al , 2012; Das et al , 2016), whereas PS1 co‐migrated with MAM markers, such as FACL4 (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). We reasoned that the difficulty in seeing APP‐CTFs and PS1 together was probably due to the rapid cleavage of the CTFs by γ‐secretase once both are in the same compartment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the data of others (Das et al , 2016), FL‐APP and BACE1 co‐migrated partially with a marker for endosomes (Rab7), but not with lysosomal, ER‐intermediate, or MAM markers (Fig 2C). Similarly, the APP‐CTFs C83 and C99 co‐migrated with endosomal and lysosomal markers (Rab5, Rab7, and LAMP‐2) (Haass et al , 2012; Das et al , 2016), whereas PS1 co‐migrated with MAM markers, such as FACL4 (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). We reasoned that the difficulty in seeing APP‐CTFs and PS1 together was probably due to the rapid cleavage of the CTFs by γ‐secretase once both are in the same compartment.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that presenilins and γ‐secretase activity localize to MAM (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). Moreover, MAM functionality (Area‐Gomez et al , 2012) and ER–mitochondrial apposition (Area‐Gomez et al , 2012; Hedskog et al , 2013) are increased in AD.…”
Section: Introductionmentioning
confidence: 84%
“…The Watanabe et al paper shows that these aberrant transcripts are not completely degraded in brain tissue although nonsense-medicated mRNA decay appears to remove them completely in other tissues. We have analyzed the putative protein products of these aberrant transcripts using assays in zebrafish embryos and have seen dominant negative effects specifically on Notch signaling but not on ␥-secretase cleavage of an A␤PP orthologue [87]. Zebrafish Psen1 peptides equivalent to those putatively translated from the aberrant transcripts also incorporate specifically and avidly into detergent-resistant higher molecular weight complexes and bind to both Psen1 and Psen2 proteins [87].…”
Section: Changes In the Level Of ␥-Secretase Activity Are Criticalmentioning
confidence: 99%
“…We have analyzed the putative protein products of these aberrant transcripts using assays in zebrafish embryos and have seen dominant negative effects specifically on Notch signaling but not on ␥-secretase cleavage of an A␤PP orthologue [87]. Zebrafish Psen1 peptides equivalent to those putatively translated from the aberrant transcripts also incorporate specifically and avidly into detergent-resistant higher molecular weight complexes and bind to both Psen1 and Psen2 proteins [87]. Therefore, it is possible that the action of truncated forms of PSEN1 protein may underlie the frontotemporal dementia pathology of the G183V mutation of human PSEN1.…”
Section: Changes In the Level Of ␥-Secretase Activity Are Criticalmentioning
confidence: 99%
See 1 more Smart Citation